Evaluación de la producción forrajera mediante la incorporación de un polímero retenedor de agua en una pastura ya establecida a base de ryegrass perenne diploide y tetraploide en la parroquia de Aláquez - Ayala Rodríguez, Edgar Mauricio (2021)
This research was carried out in the parish of Aláquez, Canton Latacunga, to evaluate forage production through the incorporation and effect of a water-retaining polymer, which was applied, without hydrating, with harrow discs at a depth of approximately 10 cm, during the dry season. The work was based on performing three gauging/cuttings on different dates to observe the behavior of the pastures with the use of hydrogel in sandy loam soils. The experimental design implemented was completely randomized for the analysis of the pastures. Two treatments were made, a coefficient of variation of 3, 46% for the use of hydrogel in pastures through ADEVA. The Tukey test at 5% showed that forage production averages for the hydrogel treatment were different from those without hydrogel. For the analysis of the climatology, measures of central tendency were calculated to use the median as a reference to determine the dry season for the months of ( June 31.4 mm; July 15.2 mm; August 12.6 mm; September 24.4 mm), for the effect of the use on the nutritional content of the treatments on the pastures, bromatological analyses were carried out. Finally, according to the trial results, hydrogel represents a low-cost technological alternative for the sector. Because it helps to maintain soil moisture and water availability for perennial ryegrass pastures (Lolium Perenne), low rainfall brings a water deficit for the different pastures and crops of the sector. It is recommended to use hydrogel as an alternative to conserve pastures during the dry season in the sector of Aláquez.